A quantitative framework for investigating risk of deadly collisions between marine wildlife and boats. Issue 1 (12th November 2015) - Martin, Julien; Sabatier, Quentin; Gowan, Timothy A.; Giraud, Christophe; Gurarie, Eliezer; Calleson, Charles Scott; Ortega‐Ortiz, Joel G.; Deutsch, Charles J.; Rycyk, Athena; Koslovsky, Stacie M.
Summary: Speed regulations of watercraft in protected areas are designed to reduce lethal collisions with wildlife but can have economic consequences. We present a quantitative framework for investigating the risk of deadly collisions between boats and wildlife. We apply encounter rate theory to demonstrate how marine mammal–boat encounter rate can be used to predict the expected number of deaths associated with management scenarios. We illustrate our approach with management scenarios for two endangered species: the Florida manatee Trichechus manatus latirostris and the North Atlantic right whale Eubalaena glacialis . We used a Monte Carlo simulation approach to demonstrate the uncertainty that is associated with our estimate of relative mortality. We show that encounter rate increased with vessel speed but that the expected number of encounters varies depending on the boating activities considered. For instance, in a scenario involving manatees and boating activities such as water skiing, the expected number of encounters in a given area (in a fixed time interval) increased with vessel speed. In another scenario in which a vessel made a transit of fixed length, the expected number of encounters decreases slightly with boat speed. In both cases, the expected number of encounters increased with distanced travelled by the boat. For whales, we found a slight reduction (˜0·1%) in the number of encounters under a scenario where speed is unregulated; this reduction, however, is negligible, and overall expected relative mortality was ˜30% lower under the scenario with speed regulation. The probability of avoidance by the animal or vessel was set to 0 because of lack of data, but we explored the importance of this parameter on the model predictions. In fact, expected relative mortality under speed regulations decreases even further when the probability of avoidance is a decreasing function of vessel speed. By applying encounter rate theory to the case of boat collisions with marine mammals, we gained new insights about encounter processes between wildlife and watercraft. Our work emphasizes the importance of considering uncertainty when estimating wildlife mortality. Finally, our findings are relevant to other systems and ecological processes involving the encounter between moving agents.